2016
DOI: 10.3390/children3040024
|View full text |Cite
|
Sign up to set email alerts
|

Practicalities and Research Considerations for Conducting Childhood Obesity Prevention Interventions with Families

Abstract: Internationally, childhood obesity is a major public health concern. Given the established difficulties in treating obesity, designing and evaluating effective obesity prevention interventions are research priorities. As parents play a crucial role in establishing positive health behaviours in children, they are a key target for child obesity prevention programs. However, recruiting and engaging parents in such interventions can be a considerable challenge for researchers and practitioners. Members of the ‘Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
15

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(57 citation statements)
references
References 60 publications
(97 reference statements)
1
41
0
15
Order By: Relevance
“…Hence, preventative measures for childhood obesity should consider family dietary habits [33,34]. To control BMI, Esfarjani et al [35] conducted a family-based intervention study in an attempt to decrease oil and sugar consumption among 156 obese children, and discovered that the family diet-style program had desirable effects.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, preventative measures for childhood obesity should consider family dietary habits [33,34]. To control BMI, Esfarjani et al [35] conducted a family-based intervention study in an attempt to decrease oil and sugar consumption among 156 obese children, and discovered that the family diet-style program had desirable effects.…”
Section: Discussionmentioning
confidence: 99%
“…The practicalities of conducting complex early childhood obesity interventions can be challenging 19 . These interventions target parent behaviours to influence or change child outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a study of Greenleaf and Weiller [44] it was found that PE teachers have lower expectations about the physical, cognition and social skills of overweight pupils. Children with overweight problems also engage in leisure-time PA less frequently and less regularly [45].…”
Section: Discussionmentioning
confidence: 99%